Impact of Environmental and Biochemical Factors on Recurrent Tonsillitis among School-Age Children: A Community-Based Clinical Study - IKRAM, Hameedullah Achakzai, Iqbal Ahmad, Farooq Ahmad Malik, Rizwan Saeed, Muhammad Athif Akram, S. M. Qaisar Sajjad (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Recurrent tonsillitis is a common childhood disorder characterized by repeated tonsillitis, which is linked to a diminished quality of life, school absence, and increased health care costs. Environmental exposures and biochemical disturbances can play a major role in the recurrence of diseases in school-age children of school age. Objective: To assess the effect of environmental and biochemical factors on the occurrence of recurrent tonsillitis in a community-based clinical population of school-age children. Materials and Methods: This community-based cross-sectional clinical study was conducted from June 2022 to June 2023 at the Department of Pediatric Medicine, Shahida Islam Teaching Hospital, Lodhran, Punjab, Pakistan, and Sir Syed College of Medical Sciences for Girls, Karachi, Sindh, Pakistan. The total number of children aged 5-15 years was 120, including 70 children with recurrent tonsillitis and 50 healthy control children. Structured questionnaires were used to evaluate environmental factors such as passive smoking, overcrowding, poor ventilation, biomass fuel exposure, and dust allergen exposure. Biochemical investigations included complete blood count, C-reactive protein (CRP), antistreptolysin O (ASO) titer, eosinophil count, serum vitamin D, serum iron, and serum calcium levels. Data were analyzed statistically with SPSS 25.0. Results: Children with recurrent tonsillitis had significantly more passive smoking, overcrowding, poor ventilation, and environmental allergens than the controls. High levels of CRP, leucocytosis, eosinophilia, and high ASO titres were significantly correlated with recurrent tonsillitis. Additionally, vitamin D deficiency and low calcium and iron levels in the serum were significantly more prevalent among the affected children. The multivariate analysis revealed that passive smoking, poor ventilation, high ASO levels, and vitamin D deficiency were independent factors for recurrent tonsillitis. Conclusion: Exposure to the environment and biochemical abnormalities play a major role in the occurrence of recurrent tonsillitis in school-age children. Identification and correction of modifiable risk factors early in life may lead to a decrease in disease recurrence and improve health outcomes in children. Keywords: Recurrent tonsillitis, school-age children, environmental exposure, vitamin D deficiency, inflammatory biomarkers, pediatric infections, ASO titer